Novel colon‐available triterpenoids identified in raspberry fruits exhibit antigenotoxic activities in vitro. Issue 2 (2nd December 2016) - McDougall, Gordon J.; Allwood, J. William; Pereira‐Caro, Gema; Brown, Emma M.; Verrall, Susan; Stewart, Derek; Latimer, Cheryl; McMullan, Geoff; Lawther, Roger; O'Connor, Gloria; Rowland, Ian; Crozier, Alan; et al.
Abstract : Two major unknown components present in ileal fluids after intake of raspberries are identified as triterpenoid glycosides and p ‐coumaroyl glucarates using LC–MS n analysis. The triterpenoids are purified from raspberries and are shown to have genoprotective effects at submicromolar levels against H2 O2 ‐induced damage in colon cell lines. Therefore these novel triterpenoids combine established colonic bioavailability with potential bioactivity at physiological doses. Abstract : Scope: Ileostomy studies provide a unique insight into digestion of food, allowing identification of physiologically relevant dietary phytochemicals and their metabolites important to gut health. We previously reported the consistent increase of components in ileal fluids of ileostomates after consumption of raspberries with use of nontargeted LC–MS n techniques and data deconvolution software highlighting two major unknown components ( m/z 355 and 679). Methods and results: In‐depth LC–MS n analyses suggested that the ileal m/z 355 components were p ‐coumaroyl glucarates. These compounds have not been identified previously and were confirmed in raspberry extracts after partial purification. The major ileal component with m/z 679 was a glycoside with an aglycone of m/z 517 and was present as two peaks in extracts of whole puree, unseeded puree, and isolated seeds. These components were purified using Sephadex LH20 and C18 SPE units and identified as major, novel raspberry triterpenoid glycosides. This triterpenoid‐enriched fraction (100 nM) protected against H2 O2 ‐induced DNA damage in both colon cancer and normal cell lines and altered expression of cytoprotective genes. Conclusion: The presence of these novel raspberry triterpenoid components in ileal fluids indicates that they would be colon‐available in vivo, so confirmation of their anticancer bioactivities is of key physiological relevance.